PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP MINAT FOTOGRAFI PADA KOMUNITAS FOTOGRAFI PEKANBARU - ADITYA, RANGGA; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Rapid technological developments in this time had impact on the occurrence of an efficient communication revolution. The development of communication technology makes the rise of new trends on the internet. Social networking media at this moment was very easier for users which using smartphones that can access internet services, such as Facebook, Twitter, Instagram, and othersResearchers was interested to studying the effects of Instagram social media on the interest of photograph on Komunitas Fotografi Pekanbaru because there were found to an influence on the mass media to users. The purpose of this study was to know the Instagram influence with interest of photograph on each member of the Komunitas Fotografi Pekanbaru.The study method that was used in this study is a explanation quantitative method. Data collection techniques in this study using a questionnaire. The number of samples for this study was 51 respondents and using sensus techniques. To determine the influence of these two variables, the researchers will use a simple linear regression analysis. And for the process of calibration questionnaire test, was performed by using the program Statistics Product And Service Solutions (SPSS) version of Windows 16.Based on these results with indicators of variables Instagram such as hastag, geotag, follow, share, like, comment, mention and variable of interest in photograph such as concern or interest, activity image capture, and documenting act. It will be obtained by the regression coefficient in this study is Y = 1,012+ 0,807 X wich is significance level was 0.01 smaller than α = 0.05. Therefore, Ha was accepted and Ho was rejected, it means that there is the influence of social media Instagram variable to variable of interest in photograph with a contribution of 63.6% strong category. The percentage was explained that it have strong influence between Instagram social media and growing of interest in photograph at Komunitas Fotografi Pekanbaru.Keyword: Social Media, Instagram, Interest of Photograph